الشيخ عبد الواحد يحي وجهوده في خدمة التصوف الإسلامي - بوخزنة, عبد الباقي (University of Eloued جامعة الوادي, 2018)
جاءت هذه الدراسة بعنوان: الشيخ عبد الواحد يحي وجهوده في خدمة التصوف الإسلامي؛ لتصف حياة وجهود أهم المتخصصين في التصوف الإسلامي، حيث بينت الدراسة مكانة الشيخ عبد الواحد يحي في الوسط الصوفي الغربي الحديث، وقد تعرضت هذه الدراسة لمعالم التجربة الروحية عنده، فبينت مفهوم التصوف في فكر الشيخ؛ والذي يعرفه بتجربة روحية عرفانية وفقط. وحددت الدراسة الشروط التي وضعها الشيخ لطالبي الانتساب للتصوف وهي: الاستعدادات الأولية، والمجاهدة، ثم الارتباط بالسلسلة الروحية، و أوضحت كيف أن الشيخ اختار الطريق الصوفي؛ المتقيد بضوابط الشريعة الإسلامية؛ وهذا ما دفعه ليقود حملة نقدية في وجه الحركات الروحانية الزائفة، وقد احتوت هذه الدراسة: مقدمة مهدت فيها للموضوع، وذكرت فيها منهج البحث وخطته، ثم فصل جعلته كأساس مفاهيمي؛ تطرقت فيه للمضامين المعرفية التي تدور حول تعريف كلمة تصوف ومراحل نشأته، ثم ناقشت مسألة أصالة التصوف الإسلامي بين المؤيد والمعارض، ثم فصل ثاني: ذكرت فيه حياة ونشأة الشيخ ودخوله للإسلام، ثم عرضت أسس الطريق الصوفي للشيخ عبد الواحد يحي؛ ونقده لأخطاء ومزالق التصوف المنتشر في هذا العصر، ثم أتممت البحث بخاتمة ضمنتها أهم النتائج. "This dissertation seeks to study the life and the efforts of Sheikh Abdul Wahid Yahya, one of the most famous specialists in Islamic Sufism. For this reason, the study was titled :""The Efforts of Sheikh Abdul Wahid Yahya in the Service of Islamic Sufism"". The aim of this study is to shed light on the position of Sheikh Abdul Wahid Yahya in the modern Western Sufism community. The study focused on the features of the spiritual experience in the thought of the sheikh, where the concept of Sufism emerges as only a spiritual ('Irfan) experience. The study also identified the conditions of affiliation to Sufism which were suggested by Sheikh Abdul Wahid Yahya : Predisposition, Self-striving (Mujāhadah), and the attachment to the spiritual chain ('Tariqa(. This research explained how the Sheikh chose the Sufi path which adheres to the rules of S'haria (Islamic law), and how he criticized the distorted Sufi movements. The study has been divided into two chapters; The problem of study and the methodology of research was presented in the introduction. The first chapter was devoted to conceptual framework, in order to discuss the concept of Sufism and its emergence stages, and then discuss the originality of Islamic Sufism between the supporters and the opponents. While the second chapter attempts to shed light on the life of Sheikh Abdul Wahid Yahya and his Sufi path foundations. In addition will be addressed his criticism of the wrong Sufism today , Finally the study conclude the research with the main results. "
مذكرة ماستر تخصص عقيدة
Keywords: الشيخ عبد الواحد يحي ، التصوف ، التجربة الروحية; Sheikh Abdul Wahid Yahya, Sufism, Spiritual experience